Design of a high performance thin all-solid-state supercapacitor mimicking the active interface of its liquid-state counterpart - Anothumakkool, Bihag; Torris, Arun A. T.; Bhange, Siddheshwar N.; Unni, SreeKuttan M.; Badiger, Manohar V.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2013)
Here we report an all-solid-state supercapacitor (ASSP) which closely mimics the electrode-electrolyte interface of its liquid-state counterpart by impregnating polyaniline (PANO-coated carbon paper with polyvinyl alcohol-H2SO4 (PVA-H2SO4) gel/plasticized polymer electrolyte. The well penetrated PVA-H2SO4 network along the porous carbon matrix essentially enhanced the electrode-electrolyte interface of the resulting device with a very low equivalent series resistance (ESR) of 1 Omega/cm(2) and established an interfacial structure very similar to a liquid electrolyte. The designed interface of the device was confirmed by cross-sectional elemental mapping and scanning electron microscopy (SEM) images. The PANI in the device displayed a specific capacitance of 647 F/g with an areal capacitance of 1 F/cm(2) at 0.5 A/g and a capacitance retention of 62% at 20 A/g. The above values are the highest among those reported for any solid-state-supercapacitor. The whole device, including the electrolyte, shows a capacitance of 12 F/g with a significantly low leakage current of 16 mu A(2). Apart from this, the device showed excellent stability for 10000 cycles with a coulombic efficiency of 100%. Energy density of the PANI in the device is 14.3 Wh/kg.
Keywords: all-solid-state; cyclic voltametry; impedance analysis; polyaniline; polyvinyl alcohol; supercapacitor